A revision and phylogenetic analysis of the spider genus Aysenia Tullgren (Araneae: Anyphaenidae, Amaurobioidinae) - Márquez, María E. González; Ramírez, Martín J. (Zootaxa, 2012)
The genus Aysenia Tullgren includes 8 species of spiders endemic to the southern forests of Chile and Argentina. Theyhave an elongated body, recurved posterior eye row and third legs directed forward. There are currently five known speciesof Aysenia. The study of all the specimens of Aysenia available in collections showed the existence of three undescribedspecies and the unknown male of A. elongata, all of which are here described. New geographical records are provided forall species, with illustrations and reviewed diagnosis for the genus and the previously known species. Data from the newspecies and the male of A. elongata are used to test the monophyly of the genus, its relationships with other genera in thefamily, and among its species. The phylogenetic analysis using cladistic methods uses observations from 264 previously defined characters plus three characters that arise from this study, scored for 104 species of Anyphaenidae.